Structural variability of sunflower gene for methionine-rich albumin SFA8 - I. N. Anisimova; N. V. Alpatieva; S. V. Goryunova; D. V. Goryunov; Al. V. Konarev; V. A. Gavrilova; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. The 2S albumins of sunflower and other oilseed plants possess a high nutritional quality, the defense activity against fungi diseases casual gents and also valuable functional properties. The major component of albumin fraction, the SFA8 protein consists of 103 amino acid residues among which methionine constitutes 15 Mole %. In the cultivated sunflower gene pool the SFA8 structural gene is represented by the two alleles the products of which have different isoelectric points and differ by the electrophoretic mobility, however molecular mechanisms of the polymorphism are still unknown. Results. The amplified sequences of the SFA8 gene from seven Helianthus annuus L. accessions and three accessions of wild Helianthus L. species from VIR collection were sequences. The intron of 258-303 bp length depending on the genotype was firstly found in the central part of the gene. The length of the first exon constitutes 99 bp, the second exon is of 210 bp length. The nucleotide and translated amino acid sequences are polymorphic among different genotypes. The line VIR 130 in which the two expressing SFA8 proteins, the normal polypeptide with isoelectric point (pI) approximately 6.0 (normal SFA8) and its allelic variant with pI 6.5 (variant SFA8) have been earlier revealed possesses two types of the SFA8 encoding sequence. In one sequence the substitution 108С—G is present that results in the substitution of the polar uncharged amino acid serine for the positively charged arginine and respectively in alteration of the protein charge and isoelectric point. The intron sequence is also polymorphic and characterized by the presence of indels of approximately 45 bp. The intron sequences of all accessions contain dinucleotides GT at the 5΄ end and AG at the 3΄ end which are characteristic for consensus sequences of splicing sites in the U2-type introns. The variants of the secondary structure of the SFA8 intron sequences of H. argophyllus Torr. & A. Gray and all the analyzed H. annuus genotypes are similar and differ from those of H. petiolaris Nutt. and H. giganteus L. Conclusions. The data on the SFA8 gene sequence polymorphism are important understanding the molecular mechanisms of genotypic differences in biochemical and functional properties of the protein, and he revealed differences in the intron secondary structure can be important for understanding expression patterns of the protein.